2021
DOI: 10.48550/arxiv.2107.04251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constraints on Weak Supernova Kicks from Observed Pulsar Velocities

Reinhold Willcox,
Ilya Mandel,
Eric Thrane
et al.

Abstract: Observations of binary pulsars and pulsars in globular clusters suggest that at least some pulsars must receive weak natal kicks at birth. If all pulsars received strong natal kicks above 50 km s −1 , those born in globular clusters would predominantly escape, while wide binaries would be disrupted. On the other hand, observations of transverse velocities of isolated radio pulsars indicate that only 5 ± 2% have velocities below 50 km s −1 . We explore this apparent tension with rapid binary population synthesi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We assume that such stars undergo an ecSN, receiving weak natal kicks drawn from the Maxwellian velocity distribution with 𝜎 = 30 km/s. In these three models we assume that ecSN occurs exclusively in stars which lost their hydrogen envelope due to mass transfer in line with original idea by Podsiadlowski et al (2004), and more recently used by Willcox et al (2021). In our models G1, H1 and J1 we also check if effectively isolated stars have helium core mass at the beginning of AGB in ranges as mentioned in Table 2.…”
Section: Assumptions For the Binary Population Synthesismentioning
confidence: 96%
See 2 more Smart Citations
“…We assume that such stars undergo an ecSN, receiving weak natal kicks drawn from the Maxwellian velocity distribution with 𝜎 = 30 km/s. In these three models we assume that ecSN occurs exclusively in stars which lost their hydrogen envelope due to mass transfer in line with original idea by Podsiadlowski et al (2004), and more recently used by Willcox et al (2021). In our models G1, H1 and J1 we also check if effectively isolated stars have helium core mass at the beginning of AGB in ranges as mentioned in Table 2.…”
Section: Assumptions For the Binary Population Synthesismentioning
confidence: 96%
“…In comparison to Willcox et al (2021), we do require ecSN to occur in effectively isolated stars. The main reason for this is that Willcox et al ( 2021) used a non-parametric description for natal kick of NSs.…”
Section: Electron Capture Supernova Explosionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andrews et al (2015) and Vinciguerra et al (2020) use different core mass ranges for ECSNe (2-2.5 M and 1.83-2.25 M , respectively, where the latter is based on Fryer et al 2012, which could better reproduce observations of NSs). Willcox et al (2021) argued that the (ZAMS) mass range of (effectively) single stars undergoing ECSNe cannot be wider than 0.2 M to avoid overproducing low velocity pulsars, but ECSNe could be more common in binaries.…”
Section: Electron-capture Supernovaementioning
confidence: 99%
“…Miller-Jones et al (2021) and Neijssel et al (2021) constrained the massive star wind mass loss with observations of the black hole (BH) high-mass X-ray binary Cygnus X-1. Willcox et al (2021) compared COM-PAS models against observed pulsar velocities in order to study neutron star natal kicks.…”
mentioning
confidence: 99%